AN ILLOCUTIONARY ACTS ANALYSIS OF OLIVIA RODRIGO’S SPEECH AT BILLBOARD’S WOMEN IN MUSIC AWARD - Purba, Raysa; Silitonga, Mega Uli Arta; br. Sirait, Naomi Sephania; Rangkuti, Rahmadsyah (Universitas Muhammadiyah Lampung, 2024)
Based on John Searle's concept of speech acts, this study examines one of three critical components of Speech Act: Illocutionary, which occurs in Olivia Rodrigo's Speech at Billboard's Women in Music Awards. The study aims to determine the various Illocutionary Acts that Rodrigo Employs, as well as the dominant Illocutionary acts. The study is based on the video of Olivia Rodrigo's Speech at Billboard's Women in Music Awards from YouTube. This video was published on March 4th, 2022. The data is collected from Illocutionary acts in Rodrigo's speech, watched on YouTube, and read from a written transcript in the YouTube subtitle. This study uses a descriptive qualitative approach to clarify the data deeply. The topic of study is the phenomena of Illocutionary acts in verbal communication or spoken language. The results revealed that 15 Illocutionary acts occur in Olivia Rodrigo's speech, and the most common one is expressive acts.Â